56-(3c+4)=4(c+7)+3

Simple and best practice solution for 56-(3c+4)=4(c+7)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 56-(3c+4)=4(c+7)+3 equation:


Simplifying
56 + -1(3c + 4) = 4(c + 7) + 3

Reorder the terms:
56 + -1(4 + 3c) = 4(c + 7) + 3
56 + (4 * -1 + 3c * -1) = 4(c + 7) + 3
56 + (-4 + -3c) = 4(c + 7) + 3

Combine like terms: 56 + -4 = 52
52 + -3c = 4(c + 7) + 3

Reorder the terms:
52 + -3c = 4(7 + c) + 3
52 + -3c = (7 * 4 + c * 4) + 3
52 + -3c = (28 + 4c) + 3

Reorder the terms:
52 + -3c = 28 + 3 + 4c

Combine like terms: 28 + 3 = 31
52 + -3c = 31 + 4c

Solving
52 + -3c = 31 + 4c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-4c' to each side of the equation.
52 + -3c + -4c = 31 + 4c + -4c

Combine like terms: -3c + -4c = -7c
52 + -7c = 31 + 4c + -4c

Combine like terms: 4c + -4c = 0
52 + -7c = 31 + 0
52 + -7c = 31

Add '-52' to each side of the equation.
52 + -52 + -7c = 31 + -52

Combine like terms: 52 + -52 = 0
0 + -7c = 31 + -52
-7c = 31 + -52

Combine like terms: 31 + -52 = -21
-7c = -21

Divide each side by '-7'.
c = 3

Simplifying
c = 3

See similar equations:

| 0.07y+0.02x=5 | | 9x-12+85=0 | | -3/4r-1 | | U^2-3v=0 | | -z/2 | | (2x+8)+(3x+16)+(4x-18)+(3x-7)+(2x+25)=720 | | 8+4v=-4 | | 4a+6-3a-2= | | S/-3=2 | | h=2*3.14*r^2+2*3.14*r*16.2 | | 25n-40=-62 | | 3/4(8y-12)= | | .75t=50 | | F(x)=12x-6 | | 8(-5+4)= | | .75t=.50 | | (2y+9)(2y+9)=81 | | (4-2j)/(2-1j) | | 5.26s-2.01=-8.94 | | -2g+7= | | -9s+18-18=18s-4-2 | | 7v+224=-84v | | 3v+9+v=2v-2+3 | | -38-37= | | 10+5x-x=10+4x+4 | | 45=26+b | | X+2+x-10=90 | | 2v+1=-3v+8v+10 | | 6u-12+2=6u-10 | | 14m-2m-2m-8m=12 | | 45=26 | | h=2*3.14*30.25+2*3.14*5.5*18.7 |

Equations solver categories